APLIKASI KOMPOS TANDAN KOSONG KELAPA SAWIT DAN PUPUK NPKMg TERHADAP SIFAT KIMIA TANAH ULTISOL DAN KADAR HARA DAUN KELAPA SAWIT (Elaeis guineensis Jacq) - Ahmad Syukri; Nelvia Nelvia; Adiwirman Adiwirman (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2019)
Low productivity of oil palm in Ultisol need to resolve by utilizing appropriate input and efficient soil management. Utilization of organic waste materials such as oil palm empty bunches (OPEB) is one of way for that. This research was conducted in Kuantan Singingi, Riau from September 2017 to February 2018. The aim of this research is to having dose of OPEB compost and NPKMg fertilizer that can optimize the value of soil chemical characters and nutrient content in leaves. The study determined the effect of composite oil palm empty bunches with cow manure (2:1(w/w)) and NPKMg (13:6:27:4) fertilizer. The study used a completely randomized design consisting of 6 levels :(2,25 kg NPKMg), (10 kg OPEB compost + 1,75 kg NPKMg), (20 kg OPEBcompost + 1,5 kg NPKMg), (30 kg OPEBcompost+ 1,25 kg NPKMg), (40 kg OPEBcompost + 1,00 kg NPKMg), (50 kg OPEB compost) per tree, each treatment was repeated 3 times. Parameters measured include soil chemical characters and nutrient content in leaves. The results of study showed, aplication 50 kg per tree TKKS compost was able to increase soil pH. Aplications (2.25 kg NPKMg, 50 kg TKKS compost, 20 kg compost TKKS + 1.50 kg NPKMg and 30 kg compost TKKS + 1.25 kg NPKMg) per tree can increase base saturation. Each treatment application for fertilization has been tested, given the same effect in all soil chemical characters tested beside pH and KB, and same effect in all leaf nutrient contents tested beside Zn.Key words : Palm Oil, Compost, OilPalmEmptyBunches, NPKMg